2012
DOI: 10.5604/15093492.1005087
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of congenital radial head dislocation. A case report.

Abstract: Congenital radial head dislocation is a rare condition which is, however, the most common of all congenital pathologies of the elbow joint. This paper is a case report on a patient presenting with moderate pain and discomfort in one of his elbow joints, both of which were found to be affected by this condition. He was treated by surgery which consisted of resection of the proximal radius and partial anterior capsulectomy of the elbow joint. This treatment led to a significant improvement in pain and elbow func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…In line with studies by Campbell et al 11. and Błoński et al .,19 our study found an increase in all patient’s ROM, including flexion (from 100 to 130 degrees), extension (from 80 to 100 degrees), pronation (from 10 to 75 degrees), and supination (from 25 to 70 degrees). The absence of ROM improvement in several studies might be explained by the soft-tissue contractures that manifested secondary to prolonged dislocation, in which the contractures still restrict the ROM despite the excision of obstructive bone 2…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In line with studies by Campbell et al 11. and Błoński et al .,19 our study found an increase in all patient’s ROM, including flexion (from 100 to 130 degrees), extension (from 80 to 100 degrees), pronation (from 10 to 75 degrees), and supination (from 25 to 70 degrees). The absence of ROM improvement in several studies might be explained by the soft-tissue contractures that manifested secondary to prolonged dislocation, in which the contractures still restrict the ROM despite the excision of obstructive bone 2…”
Section: Discussionsupporting
confidence: 93%
“…reported that excision of the radial head resulted in a decrease in elbow pain, 11 degrees increase in elbow flexion-extension, and 53 degrees increase in elbow rotation. Błoński et al 19. described similar outcomes.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…However, the treatment strategy for adult patients with CRHD remains controversial. In our review, Futami et al ( 10 ) performed rotational osteotomy of the radius; Bengard et al ( 3 ) performed radial head excision, wrist arthroscopy, and triangular fibrocartilage complex debridement; and Błoński et al ( 12 ) combined proximal radius osteotomy and partial anterior capsulectomy of the elbow joint. Despite limited improvement in pain, the overall outcomes were not ideal.…”
Section: Discussionmentioning
confidence: 99%
“…As symptoms in childhood are usually mild and many remain asymptomatic during adolescence, follow-up without intervention is the standard management ( 1 , 5 , 24 ). Most authors favor conservative treatment or observation ( 1 , 12 , 18 , 25 ). In some cases of CRHD diagnosed in childhood, closed reduction is still possible in selected cases with severe impairment of upper limb function or pain ( 12 , 26 ).…”
Section: Discussionmentioning
confidence: 99%